Increasing of oral health education knowledge after intervention psychoeducation methods in adolescents - Yubiliana, Gilang; Kusumah, Salsabila Putri; Abdurrochman, Andri (Padjadjaran Journal of Dentistry, 2023)
ABSTRACT Introduction: The technique of imparting knowledge and understanding known as "psychoeducation" combines particular knowledge with media to communicate knowledge, is professionally provided, and integrates educational and psychotherapy treatments. Given the close connection between oral health and general health, oral health should not be neglected during the pandemic. Through the use of psychoeducational techniques, dental health issues can be prevented and overcome. The objective of this study is to analyze the increase in oral health education knowledge before and after intervention using psychoeducation methods in adolescents. Methods: This research was conducted using the one group pretest-posttest design. A study sample was obtained using the Slovin formula after a population was sampled using purposive sampling. The following requirements must be met in order for students to be included in the sample: they must be concerned about their oral health, be open to participating in psychoeducation webinars, and agree to participate as research subjects. There were 86 responses in the sample. By providing a questionnaire before (pretest) and after (posttest) the intervention in oral health education using psychoeducation method, the increase in knowledge can be measured. Results: The results of the Wilcoxon signed rank test with an alpha significance of 0.05 and Asymp. Sig (two-tailed) p = 0.001 (p < 0.05), or the knowledge factors of research respondents. This revealed significant improvements in respondents' knowledge between the pre- and post-intervention periods. Conclusion: The intervention of psychoeducational methods regarding oral health education could increase knowledge in adolescents. Psychoeducational methods can help adolescents learn more about oral health.